A Perceptionist’s View on Psychoacoustics - BLAUERT, Jens (Archives of Acoustics, 2012)
Psychoacoustics is traditionally based on a world model that assumes a physical world existing independently of any observer – the so-called objective world. Being exposed to this world, an observer is impinged upon by a variety of stimuli reaching his/her sensory organs. These stimuli, if physiologicallyadequate, may cause biological transduction and signal processing in the sensory organs and its afferent pathways in such a way that finally a specific excitation of the cortex takes place, which results in sen sations to appear in the observer’s perceptual world. The sensations are understood as being subjective, since they require an observer to exist. This world model – also known as (objectivistic) realism – reaches its limits when it comes to explaining more complex phenomena of perception. Thereupon, in this paper, an alternative world model is emphasized and applied to psychoacoustics, namely the perceptionist’s model. Like realism, perceptionism has a long tradition in epistemology. It appears to be suitable to improve our understanding of perceptual organization.